ANALISIS TINGKAT EFEKTIVITAS LAPISAN FIBERGLASS DALAM MENGATASI KEBOCORAN PADA DINDING CONCRETE - Nazhif Rizaldi (2021)
Extreme weather conditions, where Indonesia is a country that has a tropical climate so that changes in temperature and weather occur very often. This has an impact on the easy occurrence of a cracking phase on the concrete wall which results in leaks in the concrete wall. Fiberglass CSM 300 is a material derived from glass fibers made by pulling and spinning glass material in the glass phase in the form of a fluid (liquid) to become thin irregular fibers with a density of 300 g/m2 which has many uses such as in wall lining, tank lining, and others. Yukalac 157 resin is a type of resin that is very suitable for hand lay up and spray up molding methods. The object of this research is a fiberglass layer of CSM 300 type using a yukalac 157 polyester resin on the surface of a concrete wall which is influenced by external factors such as changes in temperature, solar radiation, and environmental humidity which can cause moss on the surface of the concrete wall which affects the level of effectiveness of the concrete wall. The test results show that in environmental temperature testing, the fiberglass surface layer has an effective resistance to direct sunlight and rain, as well as significant changes in environmental temperature as evidenced by the absence of cracks in the test material. The results of the humidity test, the fiberglass surface layer test material has resistance to the moisture test so that moss is not overgrown on the fiberglass surface layer.